Reduce Disease Burden of Human Schistosomiasis in Asia Through Biological Control - Saleem, Sidra; Ahmed, Haroon; Siddiqui, Tooba; Kilinc, Seyma Gunyakti; Khan, Aisha; Afzal, Muhammad Sohail; Simsek, Sami (Bentham Science Publ Ltd, 2020)
Schistosomiasis is a chronic parasitic disease caused by a trematode blood fluke of the genus Schistosoma that belongs to the Schistosomatidae family. It is a neglected disease in different regions of Asia. In this review, 218 articles (between 2000 and 2017) related to the topic were collected from PubMed and Google scholar and reviewed. After thoroughly reading collected articles, due to irrelevant topic requirements, 94 articles were excluded. Articles that have data associated with Asian regions are considered. In Asia, the disease is prevalent in China, Philippines, Indonesia, Yemen, Nepal and Laos, etc. While in Pakistan, India and Bangladesh, the disease is not endemic and very few cases were reported. The disease was eliminated from Japan and Iran. The current review highlights the geographical distribution among Asian countries, transmission patterns, diagnosis, control strategies based on the use of anthelmintic plants and management practices implemented in Asia for the control of schistosomiasis. However, new implementations to treat schistosomiasis in humans should be proved to eliminate the disease finally in the future. This review emphasizes the biological control of schistosomiasis for the eradication of the disease from Asia in the near future.
Keywords: Schistosomiasis; distribution; Asia; plants; biological control